Non-ionizing 405 nm Light as a Potential Bactericidal Technology for Platelet Safety: Evaluation of in vitro Bacterial Inactivation and in vivo Platelet Recovery in Severe Combined Immunodeficient Mice - Maclean, Michelle; Gelderman, Monique P.; Kulkarni, Sandhya; Tomb, Rachael M.; Stewart, Caitlin F.; Anderson, John G.; MacGregor, Scott J.; Atreya, Chintamani D. (Frontiers in Medicine, 2020)
Bacterial contamination of ex vivo stored platelets is a cause of transfusion-transmitted infection. Violet-blue 405 nm light has recently demonstrated efficacy in reducing the bacterial burden in blood plasma, and its operational benefits such as non-ionizing nature, penetrability, and non-requirement for photosensitizing agents, provide a unique opportunity to develop this treatment for in situ treatment of ex vivo stored platelets as a tool for bacterial reduction. Sealed bags of platelet concentrates, seeded with low-level Staphylococcus aureus contamination, were 405 nm light-treated (3-10 mWcm-2) up to 8-hr. Antimicrobial efficacy and dose efficiency was evaluated by quantification of the post-treatment surviving bacterial contamination levels. Platelets treated with 10 mWcm-2 for 8-hr were further evaluated for survival and recovery in severe combined immunodeficient (SCID) mice. Significant inactivation of bacteria in platelet concentrates was achieved using all irradiance levels, with 99.6-100% inactivation achieved by 8-hr (P<0.05). Analysis of applied dose demonstrated that lower irradiance levels generally resulted in significant decontamination at lower doses: 180 Jcm-2/10mWcm-2 (P=0.008) compared to 43.2 Jcm-2/3 mWcm-2 (P=0.002). Additionally, the recovery of light-treated platelets, compared to non-treated platelets, in the murine model showed no significant differences (P=>0.05). This report paves the way for further comprehensive studies to test 405nm light treatment as a bactericidal technology for stored platelets.